2005
DOI: 10.1080/01485010590919648
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Microsurgical Methods in the Treatment of Varicocele

Abstract: & We reviewed records from patients who underwent two different microsurgical varicocelectomy methods: 147 (high inguinal (MHIV) and 65 sub-inguinal (MSIV) microsurgery) to compare the therapeutic activity and complications. Patients who had 2 different microsurgical varicocelectomies were compared according to preoperative connected vein, number of designated arteries, postoperative semen and improvement degree in hormone parameters, increased ratio related with pregnancy and complications. The ratio of impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
2
24
3
4
Order By: Relevance
“…Nonetheless, the difference between the two groups was not statistically significant. This was identical to the report of Orhan et al in Turkey [19], and was similar to the conclusion of Gontero et al [11] in which they commented that the difference of only 4 min in the duration of two operations was unlikely to be clinically significant. Accordingly, these results remind us that the difficulties of MIV and MSIV are similar regardless of anatomic or vessel differences in the two approaches, while further improvement of techniques with higher magnification is needed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nonetheless, the difference between the two groups was not statistically significant. This was identical to the report of Orhan et al in Turkey [19], and was similar to the conclusion of Gontero et al [11] in which they commented that the difference of only 4 min in the duration of two operations was unlikely to be clinically significant. Accordingly, these results remind us that the difficulties of MIV and MSIV are similar regardless of anatomic or vessel differences in the two approaches, while further improvement of techniques with higher magnification is needed.…”
Section: Discussionsupporting
confidence: 79%
“…From another perspective, the differences between our results and those of Gontero et al [11] might be partly explained by the fact that the patients included in our study were merely infertile males, while patients with other reasons for surgery were also included in their study. The duration of surgery in this study was longer than that reported by some other studies (25-52.36 min) [7,11,19]. This might be explained by the fact that the ocular magnification was only 8 in this study, thus longer surgical time was needed when compared with others using higher magnification techniques.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…7,8 Ramasamy and Schlegel 11 found that a varicocelectomy without testicular delivery has equivalent or more beneficial effects on semen parameters without affecting varicocele recurrence rates. Orhan et al 12 thought that both inguinal and subinguinal approach microsurgeries were effective methods to use for varicocelectomy. We chose to perform the inguinal varicocelectomy without testicular delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the subinguinal approach, all of the internal spermatic veins are identified and ligated under microscopy, and the testicular artery and lymphatics are preserved [41]. Several articles have argued that microsurgical inguinal varicocelectomy is the treatment of choice because this approach produces similar outcomes to the subinguinal approach via a simple surgical technique [474849]. One drawback of this approach is that it results in greater intraoperative pain when performed under local anesthesia.…”
Section: Treatment Of Varicocelesmentioning
confidence: 99%